Analysis of The Use of Rice Washing Water and Fermented Cassava Peel Waste on Population Growth of Daphnia Magna - Imroatun Nadila; Farikhah (Jurnal IPTEKS Pemanfaatan Sumberdaya Perikanan, 2023)
Daphnia magna is a potential natural food source due to its nutritional content. The availability of Daphnia magna is not always consistent, posing a challenge to fish cultivation. An alternative solution is to use rice wash water and fermented cassava peel waste as a source of nutrition for Daphnia magna. Rice wash water contains soluble nutrients, while fermented cassava peel waste is rich in nutrients from the fermentation process. This research was conducted in the Fisheries Cultivation Laboratory, 1st Floor, Universitas Muhammadiyah Gresik, in April-May 2023. The research method employed was experimental with five treatments and three replications. P1= 0% rice wash water, 100% fermented cassava peel; P2= 25% rice wash water, 75% fermented cassava peel; P3= 50% rice wash water, 50% fermented cassava peel; P4= 75% rice wash water, 25% fermented cassava peel; P5= 100% rice wash water, 0% fermented cassava peel. Data analysis used analysis of variance and least significant difference test. The results showed that treatment P3 had the highest population density with an average of 2578 individuals. Additionally, treatment P3 also yielded the highest growth rate of Daphnia magna, reaching a value of 28.35. The population distribution across all treatments predominantly showed the total length class <100µm. Overall, the water quality within the temperature range of 26-28°C and pH range of 6.5-8 indicated optimal conditions for the growth of Daphnia magna.